Peritoneal stromal endometriosis: a detailed morphological analysis of a large series of cases of a common and under-recognised form of endometriosis. Issue 6 (20th January 2009) - Boyle, D P; McCluggage, W G
Abstract : Aims: It is generally considered that an unequivocal histological diagnosis of endometriosis requires the presence of endometrioid-type glands and endometrioid-type stroma. However, small nodules or plaques of endometrioid-type stroma without glands have been noticed by the authors in repeated peritoneal biopsies performed for suspected endometriosis. These are often, but not always, accompanied by typical endometriosis with glands. This form of endometriosis has been previously referred to as stromal or micronodular stromal endometriosis. However, there has been little reference to this condition in the literature. Methods: In this study, there was a review of a large series (n = 274) of peritoneal biopsies with a diagnosis of endometriosis with a view to ascertaining the frequency of stromal endometriosis. Results: Stromal endometriosis, characterised histologically by small microscopic nodules or plaques of endometrioid-type stroma, sometimes with a whorled pattern and prominent vascularity and erythrocyte extravasation, was identified in 44.9% of the biopsies. In 6.6% of the biopsies, stromal endometriosis occurred without typical endometriosis. The foci of stromal endometriosis usually had a superficial location just beneath the mesothelial surface or protruding above this. Associated histological features present in some cases included reactive mesothelial proliferation, inflammation, giant cell or granuloma formation, haemosiderin pigment deposition, microcalcification and decidualisation and myxoid change. Conclusions: Stromal endometriosis, usually in the form of superficial nodules or plaques, is a relatively common form of endometriosis which typically occurs in association with typical endometriosis but occasionally on its own. Pathologists should be aware of the existence of this form of endometriosis, the morphological features of which may be subtle. The typical location, intimately associated with surface mesothelium, may suggest that stromal endometriosis derives from mesothelial or submesothelial cells via a metaplastic process.